Implementing Inquiry-Based Science Learning on the Topic World and its Changing of Grade 8 Students - Natnicha Duanphol; Prasart Nuangchalerm; Roswanna Safkolam (PT. Pusmedia Group Indonesia, 2024)
Although Thailand's 2008 primary education curriculum emphasizes the importance of developing critical thinking and science competencies, there is still a gap between the theory and implementation of inquiry-based learning, particularly in science learning for grade 8 students in Thailand. The objectives of this study were 1) to improve academic achievement on the topic of the world and change using the inquiry-based learning management of grade 8 students to meet the criteria of 70% of the full score, and 2) to study the satisfaction of learning management by using inquiry-based learning management. The research method used is a quantitative research method. The research tools used in the study were: 5 learning management plans with a total of 10 hours, 4 multiple-choice achievement tests with 20 questions, and satisfaction questionnaire on learning management by using inquiry-based learning as a 5-level estimation of 10 items. The descriptive statistics were used by percentage, mean, and standard deviation. The results showed that the academic achievement of grade 8 students was 15.94 or 88.89% of full score, and the students who did not pass accounted for 11.11%. Also, they had highest level of satisfaction towards learning management. The study can be used and implied to science classroom for promoting science lessons and instructional practices. The implication of the results of this study is that this approach can be an effective strategy to bridge the gap between theory and practice in the Thai science education system and can be applied to other subjects to achieve educational goals in accordance with the 2008 Basic Education Curriculum. The recommendation for the results of this study is the need for further research to explore the effectiveness of inquiry-based learning in other subjects and different grade levels in order to maximize its potential in meeting the objectives of the 2008 Thai Basic Education Curriculum.